A Bibliometric Analysis of the Landscape of Cancer Rehabilitation Research (1992–2016). (29th June 2018) - Stout, Nicole L; Alfano, Catherine M; Belter, Christopher W; Nitkin, Ralph; Cernich, Alison; Lohmann Siegel, Karen; Chan, Leighton
Abstract: Cancer rehabilitation research has accelerated as great attention has focused on improving survivorship care. Recent expert consensus has attempted to prioritize research needs and suggests greater focus on studying physical functioning of survivors. However, no analysis of the publication landscape has substantiated these proposed needs. This manuscript provides an analysis of PubMed indexed articles related to cancer rehabilitation published between 1992 and 2017. A total of 22 171 publications were analyzed using machine learning and text analysis to assess publication metrics, topic areas of emphasis, and their interrelationships through topic similarity networks. Publications have increased at a rate of 136 articles per year. Approximately 10% of publications were funded by the National Institutes of Health institutes and centers, with the National Cancer Institute being the most prominent funder. The greatest volume and rate of publication increase were in the topics of Cognitive and Behavioral Therapies and Psychological Interventions, followed by Depression and Exercise Therapy. Four research topic similarity networks were identified and provide insight on areas of robust publication and notable deficits. Findings suggest that publication emphasis has strongly supported cognitive, behavioral, and psychological therapies; however, studies of functional morbidity and physical rehabilitation research are lacking. Three areas of publication deficits are noted: research on populations outside of breast, prostate, and lung cancers; methods for integrating physical rehabilitation services with cancer care, specifically regarding functional screening and assessment; and physical rehabilitation interventions. These deficits align with the needs identified by expert consensus and support the supposition that future research should emphasize a focus on physical rehabilitation.